(untitled) (Bulletin KNOB, 1989)
The scientific interest in the Dutch artist Theo van Doesburg (1883-1931), member of De Stijl, starts in 1974. Till now in general Van Doesburg’s importance as a critical writer about new developments in the plastic arts was stressed, while his architectural oeuvre has been neglected. The exposition of his architectural drawings in Museum Boymans van Beuningen and the gathering of Van Doesburg’s articles about foreign contemporary architecture by Cees Boekraad both form a first and thorough acquaintance with this work. Van Doesburg’s first contributions to architecture (1916-17), consisting of colourful stained windows or ornamental borders are of minor importance and were later on by himself negatively subscribed as ’Biedermeier’. The first example of what he called the ’Nieuwe Beelding’, perfect result of the collaboration between artist and architect, is the holiday-house ’De Vonk’ by J.J.P. Oud (1917). Van Doesburg tried by means of colour solutions, here mainly mosaics and a tile-floor with a rotating motif in yellow, black and white, to break through the static walls of architectural space. The three colour gradations of the in- and exteriors of Hotel ’De Dubbele Sleutel’ by Jan Wils (Woerden 1918) and the housing Spangen l en V by J.J.P. Oud (Rotterdam 1918) are early examples of ’Drieklanken’ (mostly blue, green and orange), named this way analogue to the musical term triad. Also the colour compositions for smaller spaces as the ’Piano Room’ for his wife Nelly (Clamart 1924) and the ’Flower Room’ in the villa of the Count de Noailles (llyères 1924- 25) are meant ’destructive’ to break through the rigidity of the walls. More adapted to the articulation of the wall is his regular colour design for an arcade with café-restaurant at the Hague (1924). Was Van Doesburg’s contribution at the discussed projects still rather submitted to architecture, a ’colour-application’, his cooperation with Cornelis van Eesteren at Weimar marks the beginning of his full acting as architect. Their common designs for the Maison Particuliere (1923) and the Maison d’Artiste resulted in the fifth Manifesto of De Stijl ’Vers une Construction Collective’ and the exposition ’The Architects of De Stijl’ (Paris 1923). At the Maison Particuliere Van Doesburg gave colour constructive values as compared to elementary architectural qualities like plane, line, space and volume, so that colour is no longer meant to ’break’ the walls but every wall is colour. Together with the extreme openness of the plan this principle brings about a complete equivalence of all sides, inside as well as outside. Except this novelty Van Doesburg developed his contra-construction at the same Maison Particuliere. Without corners or other constructive elements the walls float in space like a colourful composition, which gives this architectural drawing a pure painting-like character (afb. 3). The Aubette at Straatsburg (1926-’28), which was designed with the artists Hans Arp and Sophie Teauber-Arp forms a superb example of the synthesis between painting and architecture. Clear outlines mark the embossed colourful planes, which, alternating with greys and whites in different hues are an excellent expression of Van Doesburg’s ideas about space and colour: ’Man doesn’t live in a construction, but in a atmosphere which is defined by limitations’, or like we know now, colourful walls.